Sedimentary Sequence, Evolution Model and Petroleum Geological Significance of Forced Regression: A Case Study of the Miocene Zhujiang Formation of the Pearl River Mouth Basin in the Northern South China Sea - Ye Yu (MDPI AG, 2021)
Using 2D/3D seismic data and a large number of drilling and logging data and applying sequence stratigraphy, seismic sedimentology, and petroleum geology concepts, the characteristics of the sedimentary sequence of the forced regression have been analysed, the migration trajectory of the coastline have been reconstructed, the evolution model of the forced regression have been presented, and the significance for petroleum geology of the forced regressive sandbodies have been discussed. The falling stage systems tract (FSST) of the Zhujiang Formation present offlap high-angle oblique foreset reflection structure in the seismic profiles of the depositional trends and turbidite fan deposits with strong amplitude mound reflection structure are developed in the downdip direction of its front. The trajectory of migration of the shoreline shows a terraced downtrend in the direction of basin. The FSST is characterized by the shelf-edge delta without topset beds. The FSST was formed in the fall of relative sea-level. Five sets of foreset beds controlled by high-frequency relative eustatic were developed, therefore ordinal regressive overlap can be observed for the five sets of shelf-edge deltas in the depositional trends. The favourable reservoirs which were located close to the upper boundary of the falling stage systems tract and the basal surface of forced regression are sandbodies of the shelf-edge delta front and wave-dominated shoreface sands and the sandbodies of the turbidite fan. Those sandbodies favour the formation of lithologic oil–gas reservoirs by means of good trap sealing conditions, excellent oil–gas reserving performance, and effective oil source communication of fracture system.